Effects of negative emotions and information perceived value on residents' risk perception during the COVID-19 pandemic: An empirical survey from China - Chen, Chaoyi; Sang, Xiaodong; Wu, Ruijun; Feng, Zhanchun; Long, Chengxu; Ye, Yisheng; Yan, Ziqi; Sun, Can; Ji, Lu; Tang, Shangfeng (Frontiers in Public Health, 2023)
Background The COVID-19 pandemic has spread rapidly and heavily hit the globe, and the mutation and transmission speed of the coronavirus have accelerated so that the world is still in danger. Thus, this study aims to investigate the participants' risk perception and explore the associations of risk perception of COVID-19 with negative emotions, information value perception and other related dimensions. Methods A cross-sectional, population-based online survey was conducted from April 4 to 15, 2020, in China. A total of 3,552 participants were included in this study. A descriptive measure of demographic information was used in this study. Multiple regression models and moderating effect analysis were used to estimate the effect of potential associations of risk perceptions. Results Those who showed negative emotions (depressed, helplessness, loneliness) and perceived video information in social media to be useful were positively correlated with risk perception, whereas individuals who perceived experts' advice to be useful, shared risk information with friends and thought that their community made adequate emergency preparation reported lower risk perception. The moderating effect of information perceived value (β = 0.020, p < 0.001) on the relationship between negative emotion and perception of risk was significant. Conclusions Individual differences in risk cognition during the COVID-19 pandemic were observed in subgroups of age level. Furthermore, the role of negative emotional states, the perceived usefulness of risk information and the sense of security also contributed to improving the public's risk perception. It is crucial for authorities to focus on residents' negative emotions and to clarify misinformation in accessible and effective ways in a timely manner.